2013
DOI: 10.1016/j.ridd.2012.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive phenotype of mathematical learning disabilities: What can we learn from siblings?

Abstract: The sensitivity of number sense as cognitive phenotype for Mathematical Learning Disabilities (MLD) was assessed in siblings of children with MLD (n = 9) and age matched children without family members with MLD (n = 63). A number line estimation paradigm was used as a measure of childrens" early number sense. In line with the triple code model of Dehaene (1992), three different presentation formats were presented. The results of the study confirmed that number line estimation was related to early arithmetic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
1
11
0
1
Order By: Relevance
“…This a follow up to Shalev et al and Desoete et al determining the familial aggregation of MLD [2,20]. The study expands the previous studies by using a longitudinal design.…”
Section: Objectivessupporting
confidence: 56%
“…This a follow up to Shalev et al and Desoete et al determining the familial aggregation of MLD [2,20]. The study expands the previous studies by using a longitudinal design.…”
Section: Objectivessupporting
confidence: 56%
“…Mathematical disabilities (MD) are defined in exactly the same way as RD, but concerning mathematical abilities (Desoete, Praet, Titeca, & Ceulemans, 2013;Geary, Hoard, Nugent, & Bailey, 2011;Landerl, Bevan, & Butterworth, 2004;Passolunghi, Vercelloni, & Schadee, 2007).…”
Section: Behavioral Inhibition In Children With Mathematical Disabilimentioning
confidence: 99%
“…Some of the interventions implemented by teachers were 1) using flashcards, 2) using traditional algorithms, and 3) using technology. In addition, Desoete et al (2013) and Praet et al (2013) suggested that teachers' knowledge plays a significant role in determining the method of intervention or type of instruction in the teaching and learning of mathematics to address the needs of students with disabilities.…”
Section: Methodology and Resultsmentioning
confidence: 99%